WAYS TO DEVELOP SPEAKING ACTIVITY OF VOCATIONAL SCHOOL STUDENTS (Zamonaviy ilmiy-texnik tadqiqotlar, 2025)
Teaching vocational school students using philological knowledge to improve their speech activity is one of the broad-scale tasks today. This, in turn, aims to improve the speech activity of students of vocational schools, to teach them to think independently, to fully express their opinions orally and in writing. The level of literacy of students, its role in social life is based on the knowledge and skills acquired in speech activity. In particular, the most important task is to improve the speech activity of students of vocational schools so that they can apply the knowledge they have acquired during their work and in practice. For this reason, this article talks about the methods, tasks, directions and results of developing the speech of students of vocational schools.